Strategi Pengembangan dalam Pemberdayaan Masyarakat Pesisir Tanjung Leidong Melalui Pengelolahan Udang Menjadi Kerupuk Udang - Indah Wulan Sari BatuBara; Annio Indah Lestari Nasution (SAFE-Network, 2023)
This research aims to determine the development strategy in empowering coastal communities. The research method used is a qualitative method with a descriptive approach. The location of this research is in the village of Tanjung Leidong. Determination of informants using a purposive technique. Data collection is done by observation, interviews and documentation. Data analysis was carried out by reducing data, presenting data, and drawing conclusions. Data validity uses triangulation techniques. Based on the research results, the development strategy for empowering coastal communities in Tanjung Leidong uses the concept of local community development, namely through the processing of shrimp into shrimp crackers. The development of the shrimp cracker business in Tanjung Leidong Village is proven to be able to improve the community's economy, therefore, the processing of shrimp crackers is important to pay attention to to maintain the quality of the shrimp crackers.